Comparison of 6 cycles of isatuximab with lenalidomide, bortezomib and dexamethasone (I-VRd) versus 3 cycles of I-VRd followed by one cycle of high-dose melphalan in newly diagnosed low-risk multiple myeloma. Protocol for a multicenter, prospective, randomized, phase II clinical trial (ELIAS-Trial) - Leitner, Theo; Shumilov, Evgenii; Schwitlick, Christina; Koch, Raphael; Hamm, Franziska; Högner, Marion; Bassermann, Florian; Weisel, Katja; Einsele, Hermann; Kortüm, Martin; Rasche, Leo; Görner, Martin; et al. (Frontiers in Hematology, 2024)
Newly diagnosed multiple myeloma patients who are eligible for transplant usually receive several induction cycles of therapy, followed by one or two cycles of high-dose melphalan and autologous stem cell transfusion. In myeloma patients, high-dose melphalan improves overall survival and progression-free survival. However, melphalan exposure increases the risk of secondary malignancies and may lead to the transformation of residual myeloma cells into more aggressive clones, which may accelerate relapse. It remains to be determined whether low-risk patients also derive additional benefit from high-dose melphalan therapy compared with less toxic regimens. Here we publish the study protocol of a multicenter, interventional, controlled, randomized, prospective and open-label phase II trial to investigate whether patients with a low-risk profile (R-ISS stage I, characterized by a low tumor burden and the absence of negative cytogenetic findings or elevated LDH levels) and a standard-risk gene expression profile (using the SKY92 GEP assay) can be sufficiently treated with intensified consolidation regimens without prior high-dose melphalan chemotherapy. The primary objective is to assess whether three cycles of isatuximab, bortezomib, lenalidomide and dexamethasone (I-VRd) followed by stem cell apheresis and three additional cycles of I-VRd will result in a non-inferior rate of complete remission (CR) combined with MRD-negativity at week 40 after the start of induction therapy compared to three cycles of I-VRd followed by standard of care treatment (such as stem cell apheresis, high-dose melphalan, and autologous stem cell transplantation). We hypothesize that this approach could reduce toxicity, cost of treatment and the likelihood of the development of a more malignant plasma cell clone, while improving overall survival (OS) and progression-free survival (PFS) in newly diagnosed low risk myeloma patients.EU Trial Number2022-500453-16-00, https://clinicaltrials.gov/study/NCT05665140, identifier NCT05665140. Registration Date: 21.07.2022.